RANCANG BANGUN SISTEM PENGAMBILAN DATA PADA PEMBANGKIT LISTRIK TENAGA SURYA BERBASIS WIRELESS FIDELITY - Riza Hadi Saputra (LPPM Politeknik LP3I Medan, 2020)
The solar cell module absorbs electrons from sunlight where the electrons are converted through a semiconductor intermediary in the solar cell module. In Kalimantan, in particular, it has the potential to install a Solar Power Plant because it is traversed by the equator. However, there are various disadvantages of the Solar Power Plant, namely the building is quite large, so it needs extra monitoring so that all the conditions of the Solar Power Plant can be known. One of the data communication methods in question is using the telemetry method or long distance communication. There are many ways for the telemetry method, one of which is to use a wireless system with a connection to a cloud storage database. In short, data in the field can be sent to users wherever they are. Data sent to previous users is sent through a cloud storage database where the data can be accessed by anyone. For data sent from the Solar Power Plant in the form of incoming and outgoing voltages as well as incoming and outgoing currents. Based on the research results, it is known that the design of the data transmission system for incoming and outgoing voltages as well as incoming and outgoing currents is made from a variety of component tools used are the solar cell module, Robotdyn Mega Wi-Fi, voltage sensor, current sensor, SCC, inverter, and battery. In the process of sending data using a Wi-Fi router, data originating from the sensor is sent to Robotdyn where inside Robotdyn there is a Wi-Fi module which will then be assisted to be forwarded via a Wi-Fi router whose internet network source uses GSM. The data sent to the cloud storage database is assisted by the PHP programming language and to display the website using the HTML programming language.